2018
DOI: 10.1002/jts.22351
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Inhibitory Control May Place Service Members at Risk for Posttraumatic Stress Disorder and Negative Parenting Behavior Following Deployment‐Related Trauma

Abstract: This study examined the mediating role of posttraumatic stress disorder (PTSD) symptoms in the association between deployment-related trauma exposure and parenting behaviors in reserve-component military service members and whether this association was contingent upon parent inhibitory control (IC). Participants were 181 postdeployed fathers and their children. Fathers completed a neurospychological test of IC and self-report measures of trauma exposure and PTSD symptoms. Measures of parenting behaviors (posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…posttraumatic stress. Prior cross-sectional studies of PTSD have documented performance deficits in the areas of inhibitory control (Falconer et al, 2008;Leskin & White, 2007;Monn, Zhang, & Gewirtz, 2018;Olff, Polak, Witteveen, & Denys, 2014;Wu et al, 2010;Vasterling, Brailey, Constans, & Sutker, 1998) and sustained attention (Shucard, McCabe, & Szymanski, 2008;Vasterling et al, 1998Vasterling et al, , 2002Wu et al, 2010), but this is the first study to document these functions in prospective research as potential pretrauma vulnerability factors. With prior cross-sectional research, it has been unclear if inhibition and attention problems are a product of PTSD symptoms, that is, that heightened arousal and reexperiencing symptoms create distractors when attempting to concentrate, affecting sustained attention and inhibitory control (Aupperle et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…posttraumatic stress. Prior cross-sectional studies of PTSD have documented performance deficits in the areas of inhibitory control (Falconer et al, 2008;Leskin & White, 2007;Monn, Zhang, & Gewirtz, 2018;Olff, Polak, Witteveen, & Denys, 2014;Wu et al, 2010;Vasterling, Brailey, Constans, & Sutker, 1998) and sustained attention (Shucard, McCabe, & Szymanski, 2008;Vasterling et al, 1998Vasterling et al, , 2002Wu et al, 2010), but this is the first study to document these functions in prospective research as potential pretrauma vulnerability factors. With prior cross-sectional research, it has been unclear if inhibition and attention problems are a product of PTSD symptoms, that is, that heightened arousal and reexperiencing symptoms create distractors when attempting to concentrate, affecting sustained attention and inhibitory control (Aupperle et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, a strong body of accumulating evidence from both civilian and military samples suggests a unique association between parental PTSD and child mental health symptoms, parent-child relationship difficulties, and increased risk for parentchild aggression (Lambert, Holzer, & Hasbun, 2014;Leen-Feldner, Feldner, Bunaciu, & Blumenthal, 2011;Leen-Feldner et al, 2013). Similarly, studies have found that parents experiencing problems with depression or emotion regulation, a possible effect of trauma symptomology, may have more difficulties with parentchild relationships (e.g., emotional distance; Brockman et al, 2016;Muzik et al, 2017;Sherman et al, 2016) and report greater child psychological/behavioral problems (Boric ˇević Maršanić, Aukst Margetić, Jukić, Matko, & Grgić, 2014;C ´orić, Klaric, Petrov, & Mihic, 2016;Gómez-Ortiz, Romera, & Ortega-Ruiz, 2016;Leen-Feldner et al, 2011;Monn, Zhang, & Gewirtz, 2018). Qualitative research documenting veteran perspectives on parenting with PTSD has indicated many have a desire for parenting classes to be available at VA (Sherman, Larsen, Straits-Troster, Erbes, & Tassey, 2015).…”
mentioning
confidence: 99%
“…Indeed, fathers’ inhibitory control was not significantly associated with their attendance at the intervention sessions in the present study. Although service members with low inhibitory control tend to have higher rates of PTSD symptoms (Monn et al., 2018), the present findings suggest that individuals with higher risk levels may benefit more from a parenting intervention in terms of PTSD symptom reduction.…”
Section: Discussionmentioning
confidence: 54%
“…In an earlier study of fathers drawn from the same sample as the current study, Monn et al. (2018) found that service members with poor inhibitory control skills were more likely to exhibit PTSD symptoms regardless of their degree of combat‐related trauma exposure, whereas individuals with average or above‐average inhibitory control only reported PTSD symptoms if they were exposed to high degrees of trauma. This finding is consistent with the assertions of Aupperle et al.…”
mentioning
confidence: 64%